Wordwall Educational Games and Elementary Students' Mathematics Learning: A Systematic Review of Interest and Critical Thinking Development - Suhartuti, Lia Indra; Wiryanto; Rahaju, Endah Budi; Mariana, Neni; Purwoko, Budi (Papanda Publisher, 2025)
This study aims to examine the effect of Wordwall-based educational game media on elementary students’ interest and critical thinking in mathematics learning. The research is motivated by the need for learning approaches that can enhance student engagement and foster higher-order thinking skills (HOTS). Digital platforms such as Wordwall provide opportunities for fun, contextual, and adaptive interactions aligned with the characteristics of mathematical content and students’ cognitive development. This study employs a systematic literature review of ten nationally indexed journal articles published between 2020 and 2024. The inclusion criteria focused on studies involving elementary school students, the use of Wordwall in mathematics learning, and outcomes related to learning interest or critical thinking. Exclusion criteria included articles lacking empirical data or those focusing on non-mathematical subjects. The results indicate that consistent use of Wordwall positively influences students’ learning interest, classroom participation, and critical thinking skills in understanding basic mathematical concepts. Interactive features such as quizzes, matching pairs, and random wheels encourage students to analyze, evaluate, and draw conclusions both independently and collaboratively. Furthermore, Wordwall has shown flexibility in supporting various learning strategies, including project-based learning, flipped classrooms, and differentiated instruction. In conclusion, the integration of Wordwall contributes to enhancing both cognitive and affective aspects of mathematics learning. Future research with experimental or mixed-method approaches is recommended to measure the real impact of Wordwall implementation in classroom contexts. Thus, Wordwall serves not only as a digital tool but as a strategic medium for fostering active and meaningful learning in the 21st century.